A novel complementary method for ultrasonographic screening of deep endometriosis: a case series of 5 patients diagnosed with transvaginal strain elastography - Gábor Szabó; István Madár; János Rigó Jr; Noémi Dobó; Nándor Ács; Attila Bokor (IMR Press, 2022)
Background: Ultrasound elastography displays information on tissue stiffness. Deep endometriotic nodules are hard fibrotic tissues. Patients are recognized as having deep endometriosis only after several years from the onset of symptoms, therefore it is important to improve diagnostic capabilities. Cases: In this case series, our purpose was to present the applicability and feasibility of transvaginal strain elastography. Five patients with various complaints compatible with endometriosis underwent transvaginal ultrasound with strain elastography. Using the 'International Deep Endometriosis Analysis' group (IDEA) protocol along with transvaginal strain elastography, preoperative examination clearly demonstrated the size and extent of deep endometriosis. Conclusion: This ultrasonographic technique was effective regardless of whether the ligaments of the female reproductive tract, or the organs of the urinary and intestinal tract were infiltrated.